Makna Dasanama Dalam Garap Catur Pertunjukan Wayang Gaya Surakarta - Suwondo Suwondo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2021)
This study aims to find the meaning of the words dasanama and their classification in catur of wayang kulit performance of Surakarta style. Dasanama is a number of vocabularies that have the same or almost the same meaning and is used in the world of puppetry to give reinforcement to the meaning of a word and can also make the catur aesthetic. Nowadays dasanama is starting to be forgotten by the young dalang, therefore it is necessary to identify, classify, and explain its meaning so that it is easy to be used by the younger generation of dalang. The analytical methods used are: (1) identifying the names of the words in catur of the wayang kulit of Surakarta style; (2) classifying dasanama words based on their word references; (3) analyzing the denotative and connotative meanings of dasanama words in catur; (4) evaluating the analysis results; (5) presenting the report; and (6) compiling scientific articles. The results of the analysis show that the dasanama are divided into the classification of gods, humans, animals, and objects.